Nanomaterial cell interactions: are current in vitro tests reliable?. (July 2011) - Hirsch, Cordula; Roesslein, Matthias; Krug, Harald F; Wick, Peter
New properties of engineered nanomaterials raise great expectations for industrial, scientific as well as medical applications. At the same time concerns among consumers regarding the safety aspects of this new technology emerge. Furthermore, among the multitude of published studies, a considerable number do not reveal reliable data. Thus, standardized, validated, reliable, robust, reproducible and intelligent testing strategies are urgently needed that address nanomaterial toxicity. This article discusses the reliability of currently used in vitro toxicity assays. It covers major problems, pitfalls and challenges of assay performance and validation. We recommend a series of different controls to improve the experimental quality and, thus, also the reliability and reproducibility of current in vitro systems. These recommendations consequently applied in the future will increase the safe and sustainable use of nanotechnoloy.